Characterization of reinforced Timber Masonry Walls in "Pombalino" buildings with dynamic tests. (1st July 2018) - Goncalves, Ana Maria Neves; Guerreiro, Luís Manuel Coelho; Candeias, Paulo; Ferreira, João Gomes; Campos Costa, Alfredo
Highlights: Innovative evaluation of the seismic vulnerability of the timber framed walls of old "Pombalino" buildings through shaking table tests. Evaluation the efficiency of the strengthening technique adopted to reduce the seismic vulnerability and to assess its applicability and evaluate the effects due to modification of the "Pombalino" walls mechanical properties. Innovative technique of simulating the mass of a facade on the perpendicular walls through a hinged metallic frame with compact masses. Abstract: After the large destruction of Lisbon due to the 1755 earthquake, the city had to be completely rebuilt. The innovative "Pombalino" buildings, named after the Prime Minister Marquis of Pombal, were then developed. This type of building is characterized by its structural interior "frontal" walls in elevated floors, composed of a timber frame with vertical and horizontal elements, braced with diagonals and masonry infill. The research presented in this paper aims at assessing the seismic behavior of the "Pombalino" buildings and proposes a strengthening technique by reinforcing the timber framed "frontal" walls. The experimental program was based on extensive dynamic testing on prototypes representative of typical "frontal" walls. The results of the dynamic tests carried out in the LNEC 3D shaking table are presented regarding the two types of tests performed: (a) seismic tests, in which the seismic action was applied with increasing amplitude in the in-plane direction; (b) dynamic identification tests, performed before the first and after each increasing amplitude seismic test, aiming at evaluating the evolution of the models' mechanical properties with increasing seismic amplitude tests. A comparison of the performance of the non-strengthened and strengthened tested prototypes is also presented.